2021
DOI: 10.1111/1462-2920.15842
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the resistome risk from cow slurry and manure microbiomes to soil and vegetable microbiomes

Abstract: In cow farms, the interaction between animal and environmental microbiomes creates hotspots for antibiotic resistance dissemination. A shotgun metagenomic approach was used to survey the resistome risk in five dairy cow farms. To this purpose, 10 environmental compartments were sampled: 3 of them linked to productive cows (fresh slurry, stored slurry, slurry-amended pasture soil); 6 of them to nonproductive heifers and dry cows (faeces, fresh manure, aged manure, aged manure-amended orchard soil, vegetables-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 84 publications
5
13
0
Order By: Relevance
“…The following tetracycline-resistance genes were identified in the present study: efflux ( tetA, tetA/B, tetG, tetH, tetC, tetL, tetA(P) ), protection ( tet(36), tet(32), tetO, tetQ, tetW, tetM, tetPB ), deactivation ( tetX ) and regulation ( tetR ) in raw manure samples. Our findings are partially in line with those of other studies (Jauregi et al, 2021). Zhang et al (Zhang et al, 2020) found tetW, tet40, tetO, tetQ , and tetC to be the most prevalent types across all analyzed raw dairy cattle manure samples, accounting for over 40% of detected ARGs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The following tetracycline-resistance genes were identified in the present study: efflux ( tetA, tetA/B, tetG, tetH, tetC, tetL, tetA(P) ), protection ( tet(36), tet(32), tetO, tetQ, tetW, tetM, tetPB ), deactivation ( tetX ) and regulation ( tetR ) in raw manure samples. Our findings are partially in line with those of other studies (Jauregi et al, 2021). Zhang et al (Zhang et al, 2020) found tetW, tet40, tetO, tetQ , and tetC to be the most prevalent types across all analyzed raw dairy cattle manure samples, accounting for over 40% of detected ARGs.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, tet genes are often placed on plasmids or inserted in transposons, facilitating their dissemination (Lima et al, 2020). Jauregi et al (Jauregi et al, 2021) regard tetM, tetO, tetW, tet32, and tetS as being of particular concern due to their high dissemination potential associated with their co-occurrence with MGEs; they also highlight tet44 and tetW/N/W, which were not detected during our study. Our results partially agree, as our data also indicates some tetracycline-resistance genes to be significantly associated with MGEs: tetM (tnpA, IS613, trfA, orf37_IS26, ISAba3, IS1111, IntI3), tetO (tnpA, trfA, orf39_IS26, orf37_IS26, ISAba3, IS1111, Tn5, IntI3, tp614, IS 613), tet32 (intI3); however, neither tetW or tetS were confirmed in samples obtained from either process.…”
Section: Tetracycline-resistance Genesmentioning
confidence: 48%
“…Moreover, sul1 , tetA , and tetX gene abundances were below the quantification limit in all treatments of lettuce plants according to ddPCR. These results were consistent with the findings of previous studies indicating that the resistome and mobilome are more diverse and abundant in rhizosphere soil than in plants after the application of organic amendments 36 , 56 , 57 . Furthermore, ordinary least squares regression models pointed to the key role of MGEs in shaping the pattern of ARGs.…”
Section: Discussionsupporting
confidence: 93%
“…The increase of tet gene abundances at AD higher temperatures could be associated with the specific groups of bacteria harboring them and their capacity to grow under these environmental conditions 35 . Also, some tet genes (i.e., tetX, tetW ) were considered genes with high dissemination potential in previous studies due to their association with MGEs 36 , 37 , and under such conditions they could be transferred among a wide range of bacteria. Remarkably, the impact of anaerobic processes on ARG reduction could be gene-specific 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug resistance has been an abundant type of ARGs in air samples such as hospitals ( Jia et al, 2020 , Wu et al, 2022 ). The multidrug efflux pump mechanisms can be attributed to its involvement in multiple bacterial functions as well, not just antibiotic efflux ( Jauregi et al, 2021 , Piddock, 2006 ). Multidrug resistance may be a normal state for most bacteria to overcome environmental stress ( Wright 2007 ).…”
Section: Discussionmentioning
confidence: 99%